The duty of disclosure by directors of their interests in company contracts - Mallach, Saville Aaron (Not Specified, 2024)
In this examination of the disclosure required of directors when they hold interests in company contracts it is necessary to briefly refer to the general duties to which directors are ordinarily subject. Parsons, dealing with the director's duty of good faith, argues that the director is a fiduciary and as such must act in good faith viz-a-viz the company of which he is a director. He formulates the principles which make up such duty of good faith as follows: I. II. "A director must not place himself or allow himself to be placed in a situation in which he has an interest or duty which conflicts with his duty to act bona fide for the benefit of the company of which he is a director", and "A director must act bona fide for the benefit of the company of which he is a director."